THE CORRELATION BETWEEN STUDENTS’ ANXIETY AND STUDENTS’ ACHIEVEMENT IN LEARNING ENGLISH - Dea Pratiwi; Sulastri Manurung (CAHAYA PENDIDIKAN, 2019)
The objective of the study was to find out the  correlation between students’ anxiety and students’ achievement in learning English. The research design was correlational research which consisted of two variables, independent and dependent variable. The sampling technique was probability sampling with cluster random sampling. The sample in this research was thirty nine students of X8 social class of SMAN 08 Batam. Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz  was addressed to check the existence of students’ anxiety. The instrument to measure the students’ achievement was a diagnostic test which consists of listening and reading comprehension test. After tested the validity and reliability of the test by using SPSS V.16.0, the researcher distributed the test to the sample. Then, the researcher analysed the correlation by using Product Moment Formula by Pearson to correlate both students’ anxiety (X variable) and students’ achievement (Y variable). The result showed that the r count or Pearson correlation was 0.092. The r table for 39 respondents is 0.312. It means that r count is lower than r table and Ha is rejected and Ho is accepted. The r count showed -0.092. Hence, there was significant negative correlation between Students’ Anxiety and Students’ Achievement in learning English at the tenth grade students of Senior High School 08 Batam.